Inhibitory Effect of the Theabrownin and Tea Polysaccharide Extracts of Dark Tea on Lipase. (June 2020) - Xu, Jingyi; Wang, Weiyi; Liang, Xing; Li, Pinwu; Zou, Yao; Du, Xiao
Abstract: In order to investigate the effect of theabrownin and tea polysaccharide of dark tea on reducing fat and weight, theabrownin and tea polysaccharide extracted from dark tea of the same level in different regions were studied in this experiment and p-nitro phenol method and enzyme kinetics method was used to analyze the inhibition effects of theabrownin and tea polysaccharide on lipase, and the inhibition mechanism of tea theabrownin and tea polysaccharide on lipase was explored. The results showed that theabrownin and tea polysaccharide of dark tea extracts had a good inhibitory effect on lipase. Among them, theabrownin extracts of Pu-erh tea had the best inhibitory effect, and the IC50 of the semi-inhibitory concentration was the smallest at 24.21mg .mL −1, which was significantly less than semi-inhibitory concentrations of theabrownin extracts from dark tea in the other three regions( P<0.01). The inhibitory effect of polysaccharide extract of Liubao tea was the best, and the IC50 of the semi-inhibitory concentration was the smallest, which was 58.57mg · mL −1 . It is not significantly different from the semi-inhibitory concentration of the tea polysaccharide of Pu-erh and Kang brick, but it was significantly greater than the semi-inhibitory concentration of Fu-brick tea polysaccharide (P <0.01).The results of kinetic studies showed that the catalyst type of tea theabrownin extract of all teas was a mixed type, which contained competitive and non-competitive type in a reversible inhibition type. The catalyst type of tea polysaccharide extract of Pu-erh tea, Liubao and Tibetan tea tea were mixed types, which contained competitive and noncompetitive type in a reversible inhibition type. The catalyst type of polysaccharide extract of Fu-brick tea was a reversible inhibition type and its inhibition type was competitive inhibition. In conclusion, the theabrownin extract of Pu-erh tea and tea polysaccharide extract of Liubao tea had the best inhibitory effect on the lipase.